1995
DOI: 10.1038/376355a0
|View full text |Cite
|
Sign up to set email alerts
|

Allelic exclusion of Ly49-family genes encoding class I MHC-specific receptors on NK cells

Abstract: An important feature of natural killer (NK) cell activity is the lysis of cells that have extinguished expression of some or all class I major histocompatibility (MHC) molecules. Accordingly, the Ly49A NK-cell antigen receptor has been shown to deliver an inhibitory signal to NK cells on encounter with Dd or Dk class I MHC on target cells. Ly49A belongs to a family of eight or more highly related, tightly linked genes. Expression of Ly49A and Ly49C, another member of the Ly49 family with distinct MHC specifici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
135
0

Year Published

1996
1996
2008
2008

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 177 publications
(142 citation statements)
references
References 27 publications
7
135
0
Order By: Relevance
“…Allelic exclusion, where only one or the other allele of Ly-49 genes is expressed in the majority of F 1 NK cells, has been observed (47)(48)(49)(50). The functional significance of Ly-49 allelic exclusion is unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Allelic exclusion, where only one or the other allele of Ly-49 genes is expressed in the majority of F 1 NK cells, has been observed (47)(48)(49)(50). The functional significance of Ly-49 allelic exclusion is unknown.…”
Section: Discussionmentioning
confidence: 99%
“…[3][4][5] Cloning and sequencing of Ly49 cDNAs showed that BALB/c NK cells share at least three Ly49-related sequences or alleles with B6 mice: Ly49a, c, and g, although the alleles have diverged and contain a significant number of differences, resulting in several amino-acid substitutions. [6][7][8] The novel activating Ly49L receptor was also found to be expressed in BALB/c mice, but was first identified in the Ly49 haplo-identical CBA and C3H mouse strains. 8,9 The finding of Ly49L supported the contention that all activating receptors have an inhibitory counterpart with a highly similar extracellular domain that has probably arisen by gene hybridization between two different Ly49 genes.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, individual alleles of these Ly49 genes are stochastically chosen for stable expression in different NK cells. Monoallelic expression of the Ly49 genes is therefore thought to be essential for generating a diverse repertoire of NK cell receptors (Held et al, 1995;Held and Raulet, 1997;Held and Kunz, 1998). More recently, the analysis of wild-type T cells and heterozygous mutant mice has revealed that individual alleles of the IL-2 and IL-4 genes are independently regulated by a stochastic process in T helper cells (HollĂ€nder et al, 1998;Bix and Locksley, 1998;RiviĂšre et al, 1998).…”
Section: Monoallelic Expression As a Results Of Stochastic Activation mentioning
confidence: 99%